2008
DOI: 10.1159/000112832
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cells Are the Major Source of Alpha-Synuclein in Blood

Abstract: Background: α-Synuclein has been directly linked to Parkinson’s disease etiology by mutations in and multiplication of its gene that result in a familial form of Parkinson’s disease. α-Synuclein has been detected in blood, and was found to be elevated in the blood of those individuals with the α-synuclein gene multiplication. Objective: A complete analysis of the level of α-synuclein in blood has not been performed. In this report, we determine the quantitative distribution of α-synuclein in the plasma and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
363
2
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(391 citation statements)
references
References 30 publications
11
363
2
15
Order By: Relevance
“…Common solutions for the detection problem such as overexpressing ␣Syn were avoided here whenever possible, as the natural steady-state condition of ␣Syn in such cells might be altered. Fresh erythrocytes, an abundant source of endogenous ␣Syn (13,14), express high levels of hemoglobin that can interfere with ␣Syn detection by immunoblotting due to similar gel migration. We reasoned that if erythrocytes are rich in ␣Syn, their progenitor cells may also be, and we thus identified the human erythroleukemia cell line HEL (15) as our initial system for development of a cross-linking protocol.…”
Section: Cross-linking Of Intact Cells Reveals Endogenous ␣Syn In Dismentioning
confidence: 99%
“…Common solutions for the detection problem such as overexpressing ␣Syn were avoided here whenever possible, as the natural steady-state condition of ␣Syn in such cells might be altered. Fresh erythrocytes, an abundant source of endogenous ␣Syn (13,14), express high levels of hemoglobin that can interfere with ␣Syn detection by immunoblotting due to similar gel migration. We reasoned that if erythrocytes are rich in ␣Syn, their progenitor cells may also be, and we thus identified the human erythroleukemia cell line HEL (15) as our initial system for development of a cross-linking protocol.…”
Section: Cross-linking Of Intact Cells Reveals Endogenous ␣Syn In Dismentioning
confidence: 99%
“…Limitations of Immunoassay-based Techniques-Several factors influence the sensitivity and reproducibility of the different assays described above, among which are nonstandardized CSF and blood plasma collection and handling protocols (for example, Barbour and others have demonstrated that such samples can easily be contaminated by ␣-syn originating from lysed red blood cells and platelets (48)), the small number of samples in some studies (37), and, most important, the great diversity of capture and detection antibodies and variability in the quality and purity of the molecular standards used by different groups.…”
mentioning
confidence: 99%
“…Alpha synuclein (α-syn) is a 140 amino acid, soluble protein found predominantly within the central nervous system (CNS), and is enriched in the peripheral nervous system and circulating erythrocytes (Barbour et al, 2008;Theillet et al, 2016;Weinreb et al, 1996). The normal role of α-syn remains unclear, however high concentrations of the protein exist within neuronal presynaptic terminals, indicating potential function(s) in synaptic transmission (Cheng, Vivacqua and Yu, 2011).…”
Section: Alpha Synucleinmentioning
confidence: 99%